School Reunion Culture in Regional Tourism Development - Ida Martinelli; Puji Santoso; Mardani Daeng Patiroy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aims to find out how the reunion culture is from the perspective of regional tourism development. The method used is a qualitative descriptive research method where data is obtained from interviews and observations of the author at reunions that have been attended, as well as by examining research related to reunions and tourism development. The study results show that school reunions, usually held by school alums at the school or somewhere in the area where the school is located, can be utilized to develop tourism in the area. Alums can be empowered to become actors who can promote tourism objects in the area to people in other areas, become motivators by providing innovative thoughts to develop regional tourism, also become facilitators who provide an understanding of tourism in the area, as well as being mediators by capturing relationships and interested investors even become investors for the development and development of regional tourism.